INITIAL REFLECTIONS ON THE POLITICS OF EXPANSION OF THE HIGHER EDUCATION IN BRAZIL: THE PHYSICALEDUCATION THE DISTANCE (Fiep Bulletin - online, 2013)
This article has as objective presents some initial reflections about the implications of the enlargement of the offer of vacancies in the Brazilian higher education it saw education the distance in the degrees in physical education. It is also intended to point some reflexes that that teaching type can have in the different fields of performance, with special emphasis for the courses of educational formation. The considerations here presented are fruit of a bibliographical study and, for being a study initial, still intends to problematize and to weave considerations on the theme. The analyses accomplished in the study demonstrated to be questionable the arguments of the democratization of the access and of the qualification of the teaching presents in the teaching programs the distance.
Keywords: education the distance; physical education; education politics